Evaluation of various estimation equations for particle-fluid interaction forces and modeling of heat transfer between particles for dem simulations - Azri, Alias (2013)
The gas-solid two-phase flow takes a very important role in various industries such as medicine manufacturing, food processing, and combustion or gasification of coal. Although these wide applications of the gas-solid two-phase flow have led to extensive researches, this phenomenon is very complicated and difficult to implement an experimental investigation of the flow characteristics. On the other hand, not only the abilities of computers, but also the numerical algorithms to solve the phenomena coupled of fluid and particles have been developed. As a result, numerical approaches have been introduced to design the powder processing industries. The numerical simulations methods for two-phase flow are basically divided into three kinds of methods, which are the Two-Fluid Model (TFM), the Discrete Element Method (DEM) and Computational Fluid Dynamics (CFD) coupling model that is simply called as the DEM, and the Direct Numerical Simulation (DNS). In the TFM, both gas phase and solid phase are treated as a fluid and solved by Eulerian method. The number of particles is not limited and it is also possible to analyze larger reactor relatively, as TFM can be incorporated into a lot of commercial code. However, the particle adherence and the applicability to simulate various small scale phenomena in powder industry problem are difficult.